Réponses

  • Omnes
  • Modérateur confirmé
2014-02-28T17:42:17+01:00
Salut,

Exercice 1:

A = 81x² - 49 - (9x + 7)(6x-5)
A = (9x + 7)(9x-7) - (9x+7)(6x-5)
A = (9x + 7 )[(9x-7) - (6x-5)]
A = (9x+7)(9x - 7 - 6x + 5)
A = (9x + 7)(3x -2)

B = (2x - 4)(8x - 1) + (8x - 10)(2x - 4)
B = (2x-4)['8x - 1) + (8x - 10)]
B = (2x-4)(8x - 1 + 8x - 10)
B = (2x - 4) (16x - 11)
B = 2(x-2)(16x-11)

C = 9 - (x+5)²
C = 3² - (x+5)²
C = (x+5+3)(x+5-3)
C = (x+8)(x+2)

D = (9x - 10)(10x-9) + (9x-10)
D = (9x - 10)(10x-9) + (9x-10)*1
D = (9x-10)(10x - 9 + 1)
D = (9x-10)(10x-8)
D = 2(9x-10)(5x-4)

E = 100x² - 64
E = (10x)² - 8²
E = (10x + 8)(10x-8)
E = 2(5x+4)(10x-8)
E = 4(5x+4)(5x-4)

F = (-x+5)² + (-x-3)(-x+4)
F = (-x+5)(-x+5) + (-x-3)(-x+4)
F = (-x+5)[(-x+5) + (-x-3)]
F = (-x+5)(-x+5-x-3)
F = (-x+5)(-2x + 2)
F = -2(-x+5)(x-1)

Bonne journée !